Association analysis of indel variants and gene expression identifies MDM4 as a novel locus for skeletal muscle hypertrophy and power athlete status - Kazan, H. H.; Kasakolu, A.; Koncagul, S.; Ergun, M. A.; John, G.; Sultanov, R. I.; Zhelankin, A. V.; Semenova, E. A.; Yusupov, R. A.; Kulemin, N. A.; Larin, A. K.; Generozov, E. V.; et al. (Experimental Physiology, 2025)
Insertions and deletions (indels) are the second most common type of variation in the human genome. However, limited data on their associations with exercise-related phenotypes have been documented. The aim of the present study was to examine the association between 18,370 indel variants and power athlete status, followed by additional studies in 357,246 individuals. In the discovery phase, the D allele of the MDM4 gene rs35493922 I/D polymorphism was over-represented in power athletes compared with control subjects (P = 7.8 × 10-9) and endurance athletes (P = 0.0012). These findings were replicated in independent cohorts, showing a higher D allele frequency in power athletes compared with control subjects (P = 0.016) and endurance athletes (P = 0.031). Furthermore, the D allele was positively associated (P = 0.0013) with greater fat-free mass in the UK Biobank. MDM4 encodes a protein that inhibits the activity of p53, which induces muscle fibre atrophy. Accordingly, we found that MDM4 expression was significantly higher in the vastus lateralis of power athletes compared with endurance athletes (P = 0.0009) and was positively correlated with the percentage of fast-twitch muscle fibres (P = 0.0062) and the relative area occupied by fast-twitch muscle fibres (P = 0.0086). The association between MDM4 gene expression and an increased proportion of fast-twitch muscle fibres was confirmed in two additional cohorts. Finally, we found that the MDM4 DD genotype was associated with increased MDM4 gene expression in vastus lateralis and greater cross-sectional area of fast-twitch muscle fibres. In conclusion, MDM4 is suggested to be a potential regulator of muscle fibre specification and size, with its indel variant being associated with power athlete status.